ANALISIS PENGARUH PERBANDINGAN TIMING INJEKSI MENGGUNAKAN VARIASI BAHAN BAKAR PERTAMAX DAN ETANOL TERHADAP PERFORMA MOTOR MATIC 110CC - Bahri, Saiful; Fahruddin, Arasy; Tjahjanti, Prantasi Harmi; Iswanto, Iswanto (Otopro, 2025)
The application of ethanol as an alternative fuel needs to be continuously studied to face the energy crisis and environmental crisis. This study aims to determine the comparison of injection timing using pertamax and ethanol variations on torque, power, and efficiency in a 110cc automatic motorbike. Testing was carried out experimentally with variations in the percentage of pertamax ethanol mixture of: 15:85, 30:70, 45:55, 60:40, 70:30, and 80:20. Injection timing was modified using ECM software. Torque and power testing used a dynotest tool. The test results showed that power increased by 1.01 kW in the E45 mixture compared to standard timing, with SFC reaching 0.125 kg/kWh.